QUALITY OF CUSTOMER SERVICE FOR BUY THE SERVICE (BTS) TRANSPORTATION OF TRANS MAMMINASATA BUS FRIENDS IN MAKASSAR CITY - Sakawati, Herlina; Muswar, Irza Fachrul; Akib, Haedar (Universitas Negeri Makassar, 2024)
Irza Fachrul Muswar, 2023. Quality of Buy The Service (BTS) Transportation Services for Trans Mamminasata Bus Friends in Makassar City. Thesis, Faculty of Social and Legal Sciences, Public Administration Study Program, Makassar State University. Supervised by Herlina Sakawati and Haedar Akib. This research aims to determine the quality of Buy The Service (BTS) transportation services for Trans Mamminasata Bus Friends in Makassar City. To achieve this goal, researchers used data collection techniques through interviews, observation and documentation. The data obtained from the research results were processed using qualitative analysis to determine the quality of Buy The Service (BTS) Teman Bus Trans Mamminasata transportation services in Makassar City. The results show that the Quality of Buy The Service (BTS) Transportation Services for Trans Mamminasata Bus Friends in Makassar City is running well. This is proven based on the results of interviews, observations and documentation carried out. In several indicators according to Parasuraman et al. in Tjiptono (2000, p. 70). namely Tangibles (Physical Evidence), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Guarantee), and Empathy (Attention). However, the Tangibles (Physical Evidence) and Reliability indicators still need to be improved.